Data for: Herbivore-shrub interactions influence ecosystem respiration and BVOC composition in the subarctic - Brachmann, Cole; Vowles, Tage; Rinnan, Riikka; Björkman, Mats; Ekberg, Anna; Björk, Robert (University of Gothenburg, 2023)
Data deposited in association with above named article to be published in the journal: Biogeosciences. Biogenic Volatile Organic Compound (BVOC) data covers full processing from retention times, comparison to standards and quantification of relevant compounds. Ecosystem respiration data has already been converted to flux (linear increase in concentration of carbon dioxide (CO2) over time over sampling period). Plant Root Simulator (PRS) probe, moisture, and temperature data listed for each site and treatment. Vegetation community described for each community based on percent cover of each species.

Data om biogena flyktiga organiska föreningar (BVOC) omfattar fullständig bearbetning från retentionstider, jämförelse med standarder och kvantifiering av relevanta föreningar. Ekosystemrespirationsdata är konverterade till flöde (linjär ökning av koncentrationen av koldioxid (CO2) över tid under provtagningsperioden). Plant Root Simulator (PRS), fukt- och temperaturdata är listade för varje provyta och behandling. Vegetationsdata beskrivs för varje växtsamhälle baserat på procentuell täckning av varje art.
Data för: Herbivore-shrub interactions influence ecosystem respiration and BVOC composition in the subarctic
Keywords: ARCTIC TUNDRA; herbivory; carbon emission; ecosystem respiration; biogenic volatile organic compound; vegetation survey; Koenigia islandica; dvärgsyra; Poaceae; gräsväxter; Cladonia cornuta; syllav; Botrychium lunaria; månlåsbräken; Alectoria nigricans; upprätt tagellav; Cetraria; islandslavar; Hierochloë odorata; doftmyskgräs; Erigeron uniflorus; fjällbinka; Betula nana; dvärgbjörk; Festuca rubra; rödsvingel; Salix herbacea; dvärgvide; Jungermanniales; Trichophorum cespitosum; tuvsäv; Cladonia arbuscula; gulvit renlav; Carex brunnescens; nickstarr; Nephroma arcticum; norrlandslav; Carex bigelowii; styvstarr; Potentilla crantzii; vårfingerört; Carex dioica; nålstarr; Dicranum; kvastmossor; Ochrolechia frigida; nordlig örnlav; Taraxacum; maskrosor; Anthoxanthum; vårbroddssläktet; Anthoxanthum odoratum; sydvårbrodd; Festuca ovina; fårsvingel; Betula pubescens; glasbjörk; Cladonia furcata; rislav; Ptychostomum pseudotriquetrum; myrbryum; Ranunculus nivalis; fjällsmörblomma; Carex atrata; svartstarr; Sorbus aucuparia; rönn; Salix lanata; ullvide; Poa pratensis; ängsgröe; Sibbaldia procumbens; dvärgfingerört; Solorina crocea; saffranslav; Polytrichastrum alpinum; nordlig björnmossa; Stereocaulon; påskrislavar; Pinus sylvestris; tall; Juniperus communis; en; Polytrichum; björnmossor; Peltigera; filtlavar; Pinguicula alpina; fjälltätört; Luzula pilosa; vårfryle; Salix lapponum; lappvide; Barbilophozia lycopodioides; skogslummermossa; Huperzia selago agg.; lopplummer (aggregat); Meesia uliginosa; svanmossa; Polytrichum piliferum